Introduction. Issue 466 (4th March 2017) - Fitzpatrick, Mark
Abstract : 'This is a clear-eyed assessment of the Iran nuclear deal and how it was working smoothly before President Trump's reckless withdrawal. No single volume makes better use of the facts to refute the criticisms levied by the Trump administration against the deal, or differentiates more clearly between those of Iran's ballistic missiles which could be allowed in a negotiated arrangement and those which should be prohibited.' Angela Kane, Senior Fellow, Vienna Center for Disarmament and Non-Proliferation; former UN High Rentative for Disarmament Affairs and UN Under-Secretary-General for Management 'No one has contributed more to the public understanding of the complexities of nuclear proliferation and the attempts of various states to break out from the Non-Proliferation Treaty than Mark Fitzpatrick. Now he and his colleagues at the IISS have turned their focus to the withdrawal of the US from the JCPOA. Their new study is required reading for anyone concerned that this action could lead to yet another conflict in the Middle East or increase the risk of nuclear weapons spreading in the region.' IISS In July 2015, eight parties – France, Germany and the United Kingdom, together with the European Union and China, Russia and the United States on the one side, and Iran on the other – adopted the Joint Comprehensive Plan of Action (JCPOA), better known as the Iran nuclear deal. Under the agreement, Iran accepted limits to its nuclear programme and stricter international monitoring in return for sanctions relief. Detractors, however, saw the deal as overly lenient towards Tehran. Donald Trump described the JCPOA as the 'worst deal ever', and announced in May 2018 that the US would cease waiving sanctions and withdraw from the agreement. This Adelphi book argues that the unilateral withdrawal from the JCPOA was a grave error. Drawing on a deep understanding of the non-proliferation regime and their own technical expertise, the authors evaluate the principal criticisms of the JCPOA, some of which are unrelated to nuclear issues. The authors argue that the Procurement Channel – established by the JCPOA to give Iran a route to procure goods and services for its now-limited nuclear programme – has been an effective check on Iran's illicit procurement of nuclear-related goods. They also show that Iran's nuclear and ballistic-missile programmes are not intrinsically linked, for not all of its missiles were designed to be nuclear-capable. The fate of the JCPOA now hangs in the balance; its survival will ultimately depend on Iran.